How knowledge time influenced anxiety, depression, stress and quality of life levels in patients suffering from Crohn disease: a cross-sectional multicenter study: Anxiety, depression, stress and quality of life levels in patients suffering from Crohn disease - Vitale, Elsa; Lupo, Roberto; Artioli, Giovanna; Lezzi, Alessia; Secondo, Daniela; Mignone, Annarita; Calabrò, Antonino; Carvello, Maicol; Caldararo, Cosimo; Lezzi, Pierluigi; Scupola, Giovanni Maria; Zacchino, Simone; et al. (Acta Biomedica Atenei Parmensis, 2023)
Background and aim of the work. The diagnosis of Crohn Disease (CD) represents a turning point in the life of patients, which inevitably marks them. The present study represents a direct "feed-back" from patients suffering from Crohn disease, in order to reveal how the diagnosis of CD changed lifestyles and psychological conditions in their patients. Methods.  An observational, cross sectional, online, snowball sampling study was conducted through participants suffered from CD and belonged to social networks and Facebook groups. For each participant, sampling characteristics, a series of lifestyle habits Before to After the diagnosis of CD and anxiety, depression, and stress conditions were investigated. Results. A total of 785 participants agreed to participate. As Participants underwent significant challenges in their lifestyles after the CD diagnosis (p